Resistance of gloves and protective clothing materials to permeation of cytostatic solutions - Sylwia Krzemińska; Małgorzata Pośniak; Małgorzata Szewczyńska (International Journal of Occupational Medicine and Environmental Health, 2018)
Objectives The objective of the work was to determine the resistance of selected protective clothing and glove materials to permeation of cytostatics such as docetaxel, fluorouracil, and doxorubicin.